Novel glucose-lowering agents that benefit diabetic foot: icing on the cake - Li, Qin; Yu, Shiyan; Rui, Shunli; Lin, Xiaobu; Yuan, Yi; Armstrong, David G.; Xu, Yi; Deng, Wuquan (Frontiers in Endocrinology, 2025)
The prevalence of diabetes mellitus is increasing and is linked to several complications, including diabetic foot. Novel glucose-lowering agents are sought that also have beneficial effects in reducing diabetic complications. Among the novel glucose-lowering agents demonstrating clinical promise, three classes stand out: dipeptidyl peptidase-4 inhibitors (DPP-4is), glucagon-like peptide-1 receptor agonists (GLP-1RAs), and sodium-glucose cotransporter-2 inhibitors (SGLT2is). Some of these agents provide cardiovascular and kidney benefits, and there is evidence suggesting they also offer protective effects against diabetic foot complications. In this review, we summarize the preclinical and clinical evidence proof these three glucose-lowering agents for diabetic foot, highlighting their potential in enhancing diabetic wound healing and limb preservation. In conclusion, existing available trials have shown that certain DPP-4is and GLP-1RAs possess protective effects against diabetic foot conditions. However, SGLT2is have not demonstrated a significant protective effect. We encourage larger-scale studies on the protective effects of these three types of drugs for diabetic foot to guide physicians in providing personalized treatment strategies, achieving blood glucose targets, and promoting the healing of chronic wounds in patients.